1994
DOI: 10.1097/00005082-199404000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cellular signals in atherosclerosis

Abstract: Atherosclerosis is a complex, incompletely understood process involving several cell types, including smooth muscle cells, endothelial cells, and platelets, and the signals between them. Atherosclerotic lesions result from an excessive inflammatory fibroproliferative response to various forms of insult to the endothelium and smooth muscle of the artery wall. Numerous growth regulatory molecules/factors participate in this process. This article reviews the atherosclerotic process and provides new scientific ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is commonly recognized that low-density lipoproteins (LDLs) initiate atherosclerosis when they come in contact with monocytes/macrophages and T lymphocytes in the intimal layer of the arterial wall. [4][5][6][7] CRP may be involved in the earliest stages of atherosclerosis. Pasceri et al showed in their laboratory experiments that CRP causes the upregulation of adhesion receptors on intimal endothelial cells and promotes chemotaxis, recruiting both macrophages and T lymphocytes.…”
Section: Crp's Role In Atherogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly recognized that low-density lipoproteins (LDLs) initiate atherosclerosis when they come in contact with monocytes/macrophages and T lymphocytes in the intimal layer of the arterial wall. [4][5][6][7] CRP may be involved in the earliest stages of atherosclerosis. Pasceri et al showed in their laboratory experiments that CRP causes the upregulation of adhesion receptors on intimal endothelial cells and promotes chemotaxis, recruiting both macrophages and T lymphocytes.…”
Section: Crp's Role In Atherogenesismentioning
confidence: 99%
“…3 The inflammatory response is a complex interaction of cells, cytokines, hemodynamics, and local and systemic responses. [4][5][6][7] Insight into the role of CRP may be useful for the healthcare professional in promoting self-care and disease prevention.…”
mentioning
confidence: 99%
“…In addition, MCP-1 contributes to development of cardiovascular conditions [56] including heart failure [57]. Similarly, IFN-α is important in cardiovascular conditions [58,59] and also plays an important role in anti-viral defense, especially against Hepatitis virus type C and B [60][61][62], it contributes to the modulation of inflammatory conditions [58], has an anti-cancer effect [63,64] and plays an important role in the influenza infection process [65].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines exert both pro-and antiatherogenic actions [5]. These factors constitute an endless list of which well documented cytokines with their cell(s) of origin are listed in Table 1 [56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%